STRATEGI KEBERLANJUTAN PERGURUAN TINGGI SWASTA DI TENGAH PENURUNAN JUMLAH MAHASISWA DAN KETERBATASAN SUMBER DAYA: STUDI KASUS PADA STIE PUTRA TIMOR KUPANG - Noberth Semuel Atti; Roby Yusuf Bekuliu; Ade Tjahyono Bakri; Regina Hingi Hayong (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2026)
Private higher education institutions (PHEIs) in Indonesia are facing significant challenges, including declining student enrollment, limited human resources, and insufficient operational funding support. These challenges are also experienced by STIE Putra Timor Kupang, which has encountered a decline in student enrollment over the years, limitations in academic and administrative staff, and instability in operational funding. This study aims to analyze sustainability strategies that can be implemented by STIE Putra Timor Kupang to maintain its institutional existence and enhance its competitiveness. The study employed a qualitative method using a case study approach. The research participants consisted of institutional leaders, lecturers, administrative staff, students, and foundation board members. Data were collected through in-depth interviews, observations, and document analysis. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the sustainability of STIE Putra Timor Kupang is influenced by four main factors: educational marketing strategies, institutional governance strengthening, human resource optimization, and diversification of revenue sources. The recommended sustainability strategies include digital marketing transformation, the development of market-oriented academic programs, partnerships with government agencies and industry, strengthening a quality culture, and the establishment of campus-based business units. This study contributes to the understanding of how private higher education institutions can formulate adaptive strategies to respond to the dynamic challenges of competition in the higher education sector.